PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNGAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE LISTENING TEAM PADA PEMBELAJARAN IPAS DI KELAS IV SDN 01 BANDAR BUAT KOTA PADANG - Sarah Ibrahim; Arwin; Mansurdin; Afriza Media (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low learning outcomes of fourth-grade Public elementary school students at 01 Bandar Buat in Padang, became the basis for conducting study. Problem arose due to the lack of optimization in implementing group-based learning as a means of discussion among students and the limited use of innovative learning models during classroom activities. This situation led to low of students motivation and boredom in learning because of the limited variety in learning activities and the students’ weak understanding of the concepts because they lacked confidence in working with peers. The purpose of this study is to improve students’ learning outcomes through the use of the Listening Team Cooperative Learning Model in IPAS instruction in Grade 4 at SDN 01 Bandar Buat, Padang. Using Classroom Action Research (CAR) with qualitative and quantitative approaches. The research instruments consisted of tests and non-tests. The results of research showed that study an improvement in IPAS learning outcomes from the implementation of Cycle I to Cycle II. In Cycle I, students achieved a mean learning outcome of 77.21%, which increased 96.29% in Cycle II. There was an improvement in students’ learning outcomes from Cycle I to Cycle II by 86.78%. This indicates that the application of this model in classroom learning activities has an impact that can improve student learning outcomes, wherein the classroom serves as a forum for discussion by involving students so they can actively participate, think critically, and collaborate with their peers in learning activities, enabling them to thoroughly understand the material presented.